Is there an EU Copyright Jurisprudence? An Empirical Analysis of the Workings of the European Court of Justice. Issue 1 (15th January 2016) - Favale, Marcella; Kretschmer, Martin; Torremans, Paul C.
Abstract : The Court of Justice of the European Union has seen a dramatic and controversial increase in copyright cases during the last decade. This study investigates empirically two claims: (i) that the Court has failed to develop a coherent copyright jurisprudence (lacking domain expertise, copyright specific reasoning, and predictability); (ii) that the Court has pursued an activist, harmonising agenda (resorting to teleological interpretation of European law). We analyse the allocation of copyright and database right cases by Chambers of the Court, Advocate General (AG) and Reporting Judge, and investigate the biographical background of the Judges and AGs sitting. We trace patterns of reasoning in the Court's approach through quantitative content analysis. Legal topoi that are employed in the opinions and decisions are linked to the outcomes of each case.